Adjuvant radiotherapy does not affect hemostasis. (3rd April 2019) - Begtrup, Katrine Munk; Hojbjerg, Johanne Andersen; Offersen, Birgitte Vrou; Hvas, Anne-Mette
Abstract: Cancer is associated with increased risk of venous thromboembolic disease. Venous thromboembolic disease accounts for a substantial addition to morbidity and mortality rates in cancer patients and is the second leading cause of death in cancer patients, exceeded only by the underlying cancer. Only few previous studies have investigated the influence of radiotherapy on hemostasis and whether radiotherapy in itself causes an increased risk of venous thromboembolic disease. The aim was to investigate if adjuvant radiotherapy affects hemostasis after surgery and chemotherapy in patients with breast cancer. Radiotherapy consisted of either 40 Gy/15 fractions or 50 Gy/25 fractions. Blood samples were obtained from 39 consecutive women before and immediately after the first, the intermediate, and the final radiation fraction. Platelet function was measured using impedance aggregometry, and thrombin generation was determined in platelet-poor plasma using calibrated automated thrombogram. Furthermore, P-selectin, international normalized ratio, fibrinogen, activated partial thromboplastin time, coagulation factor VIII, von Willebrand factor, C-reactive protein (CRP), and soluble thrombomodulin were measured before and after radiation treatment. Platelet aggregation was within reference interval before initiation of radiotherapy, and remained unaffected during the radiation course. Neither serum P-selectin, thrombin generation, fibrinogen, coagulation factor VIII, von Willebrand factor, CRP nor thrombomodulin were substantially influenced by radiation treatment. The present study showed that radiotherapy did not affect hemostasis, neither by a single radiation dose nor during the radiation course, in early breast cancer patients receiving adjuvant radiotherapy.